Model Konseling Realitas untuk Mengembangkan Keterampilan Pengambilan Keputusan Karier - Andreas Rian Nugroho; Mamat Supriatna; Amin Budiamin (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2017)
This study aimed to find out the effectiveness of  reality counseling in developing students’ career decision making skill.  This study employed quasi-experimental study with non-equivalent control group design. The data were collected by using Career Decision Making Skill scale. The subjects of this study were thirty students of SMAN 1 Karangnongko. This study employed purposive sampling technique. The data were analyzed by using Mann-Whitney statistical formula. The result of this study showed that counseling reality was effective to develop students’ career decision making skill. This study generated a new counseling strategy for counselor in developing career decision making.